The early animal radiation: insights from interpreting the Cambrian problematic fossils - Cong, Peiyun (Frontiers in Earth Science, 2023)
Genic and genomic data have been reshaping our understanding of the earliest radiation event of metazoans, the well-known Cambrian Evolutionary Radiation, not only from the respects of reshuffling the phylogenetic topologies of some animal phyla but by deciphering the deep homologies of many morphological features. These advances, together with the continuing discoveries of the Ediacaran-Cambrian fossils, are unveiling the cladogenetic process of the early metazoans and the patterns of morphologic evolution during this biological radiation event. In this review, I focus on a small but challenging field, the problematic fossils from the early Cambrian fossil Lagerstätten, such as the Chengjiang biota, mainly on the controversies concerning their interpretation and the consequent impacts on understanding the early evolution of animals. The bizarre body plans of the early Cambrian problematica alone do not account for the difficulties in studying their biology and affinity. Instead, it is the combined action of the taphonomic artifacts and the uncertainty in homologizing the preserved characters that impede generating plausible interpretations. Despite all these issues, a testable and repeatable method for interpreting fossils has emerged and is becoming more practicable. The integration of an evolutionary-grade conceptual frame is beneficial to the interpretation of the Cambrian problematic fossils. Together with the focus on taphonomic alternation and homologic assessment, the Cambrian problematic fossils are becoming more informative nodes in the “parsing tree” of early animal evolution.